Investigation on the awareness of Greek Citizens regarding the Electronic Health Records - Kareklas, Nikolaos; Beleris, Aggelos; Giannakopoulou, Fani (Journal of Integrated Information Management, 2024)
Purpose - This paper aims to examine Greek citizens’ awareness regarding the necessity of transitioning from the traditional medical record to the Electronic Health Record. Design/methodology/approach - The research methodology was based on bibliographic and qualitative tools to achieve the above purpose. As a research tool was chosen a questionnaire with closed-ended questions. The sample consisted of 100 Greek citizens who were selected through a random sampling method. For the data analysis, the statistic software SPSS (Statistical Package for Social Sciences) version 23 was used. Restrictions - The study is subject to certain restrictions, in particular, due to the way the questionnaire is distributed via e- mail, which means that it is aimed at citizens who have access to the internet and the use of e-mail. Another limitation is that the sample comes from the region of Attica and not from all regions of Greece, a fact that may have affected the results of the research, as the citizens of the decentralised areas may be less informed about the Electronic Health Record. In addition, another limitation is the inability of health professionals to collect data, which does not allow clear conclusions to be drawn regarding the use of EHR and the benefits of using it to upgrade health services. Findings - Women agree more than men that the Electronic Health Record will contribute to saving time, cost, and error reduction in the medical system (p-value=0,008) and that the Electronic Health Record guarantee a better, more reliable and faster organisation of health care. (p-value=0,005). An interesting finding is that the younger participants with higher education levels had a more positive opinion about the advantages arising from the implementation of the Electronic Health.